SISTEM INFORMASI AKADEMIK BERBASIS WEB MOBILE SEBAGAI TATAKELOLA MANAJAMEN SEKOLAH PADA MTS MIFTAHUL HUDA SUKOREJO - Fitrian, Yuri; Maulana, Arbi; Anggraeni, Leni (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2021)
The mobile web-based academic information system makes it very easy to get or access information, so at MTs Miftahul Huda Sukorejo it is necessary to have a mobile web-based academic information system. Because the information has become a necessity for today's society, smartphones are the people's choice to access information on a mobile basis. The research that will be carried out is to design a mobile web-based information system that can run efficiently and effectively and can facilitate information for users. By using the SDLC method, the researcher tries to solve the problem of the academic information system at MTs Miftahul Huda Sukorejo. The design of a mobile web-based academic information system will provide easy information and academic services for parents and teachers at MTs Miftahul Huda Sukorejo